(x+1)²=
(x+y+1)²=
(x+3)(x-3)=
Răspunsuri la întrebare
Răspuns de
2
(x+1)²= x²+2x*1+1² = x²+2x+1
(x+y+1)²=x²+y²+1²+2xy+2x*1+2y*1 = x²+y²+1+2xy+2x+2y
(x+3)(x-3)=x²-3² = x²-9
(x+y+1)²=x²+y²+1²+2xy+2x*1+2y*1 = x²+y²+1+2xy+2x+2y
(x+3)(x-3)=x²-3² = x²-9
Răspuns de
1
(x + 1)² = x² + 2x + 1
(x + y + 1)² = x² + y² + 1 + 2xy + 2x + 2y
(x + 3)(x - 3) = x² - 9
(x + y + 1)² = x² + y² + 1 + 2xy + 2x + 2y
(x + 3)(x - 3) = x² - 9
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Chimie,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă